2012
DOI: 10.1177/1039856212447965
|View full text |Cite
|
Sign up to set email alerts
|

Teaching the clinical encounter in psychiatry: a trial of Balint groups for medical students

Abstract: Short-term clinical reflection groups can be effectively implemented for medical students in a hospital environment. These groups have the potential to support students in the process of learning to work in doctor-patient relationships, but may encounter significant challenges necessitating adaptation of method and process to context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 8 publications
2
39
0
Order By: Relevance
“…The overall quality of evidence was mixed (Table 2). Three out of four of the quantitative studies were found to be at high risk of bias (Brazeau et al 1998;Yakeley et al 2011;Parker & Leggett 2012). The non-randomised controlled trial was judged to have a low risk of bias for the majority of domains but lacked information about missing outcome data (Airagnes et al 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall quality of evidence was mixed (Table 2). Three out of four of the quantitative studies were found to be at high risk of bias (Brazeau et al 1998;Yakeley et al 2011;Parker & Leggett 2012). The non-randomised controlled trial was judged to have a low risk of bias for the majority of domains but lacked information about missing outcome data (Airagnes et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative analyses identified perceived improvements in relationships with patients (Torppa et al 2008;Stockmann 2015). Mean scores on Likert scale questionnaires were neutral to mildly positive about the improvement in usefulness to patients, communication skills and aspects of thought or practice (Parker & Leggett 2012;Stockmann 2015;O'Neill et al 2016), with mildly increased recognition of the inherent value of the consultation (O'Neill et al 2016).…”
Section: Therapeutic Alliancementioning
confidence: 98%
See 1 more Smart Citation
“…Hence, designing the intervention required the in-depth and extensive teamwork of three subject experts to plan and execute the training course. 42 The Balint seminar has been used in family medicine and oncology residencies to improve and strengthen the patient-doctor relationship, improve the physician's communication skills and decrease burnout, and improve job satisfaction and well-being. 7 Balint groups provide a structured process of clinical reflection, through which a doctor's experience of the relationship with a patient can be safely discussed and professionally considered by peers for constructive comments and mutual support.…”
Section: Examples Of Residents' Comments Made In Balint Sessions Twmentioning
confidence: 99%
“…41 Parker and Leggett quoted studies that advocated the educational value of Balint group for medical students in building communication and empathic skills. 42 The Balint seminar has been used in family medicine and oncology residencies to improve and strengthen the patient-doctor relationship, improve the physician's communication skills and decrease burnout, and improve job satisfaction and well-being. 43 The sessions allowed residents to see things from the patients' perspective, generating new thoughts and ideas for managing troublesome patients.…”
Section: Examples Of Residents' Comments Made In Balint Sessions Twmentioning
confidence: 99%